2017
DOI: 10.1016/j.ijadhadh.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Using the 3-point bending method to study failure initiation in epoxide-aluminum joints

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 17849 A B S T R A C TThe increasing use of adhesives in industry has boosted the search for tests which allow the adherence level to be defined. These tests, depending on the type of load, examine different stresses, failure modes and mixed modes. Furthermore, these tests can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
(37 reference statements)
1
21
0
Order By: Relevance
“…This is also in good agreement with the cross-eut test results obtained after ageing by immersion in water. We note that the measurement uncertainties are of the same order as those seen in the literature [24). During the seven days of ageing, water molecules, with their small size, can act as plasticizers in the system, which results in a diminution of the mechanical cohesion of the studied system [25).…”
Section: Information and Resultsmentioning
confidence: 78%
“…This is also in good agreement with the cross-eut test results obtained after ageing by immersion in water. We note that the measurement uncertainties are of the same order as those seen in the literature [24). During the seven days of ageing, water molecules, with their small size, can act as plasticizers in the system, which results in a diminution of the mechanical cohesion of the studied system [25).…”
Section: Information and Resultsmentioning
confidence: 78%
“…Although less used, Weibull analysis showed that the 3PBT was the most reliable for interface cracking debonding. Furthermore, the 3PBT produces a located adhesive failure initiation [6][7][8], and for these reasons, this study selected the 3PBT test for analyzing the interface debonding.…”
mentioning
confidence: 99%
“…These results cannot by vastly explored, since the critical load depends on substrate thickness. For a first general approach, Sauvage et al (2017) [8] proposed an energy-based approach, in which the dissipated energy was computed using the Euler-Bernoulli beam theory for different substrate thicknesses. Even if a located initiation zone was present, Sauvage's methodology did not consider the debonding surface.…”
mentioning
confidence: 99%
“…The two main parameters of the adherence force have been shown to be the substrate thickness and the shape of the adhesive cube [34].…”
Section: Three-point Bending Test (Afnor Iso 14679:1997)mentioning
confidence: 99%